2019
DOI: 10.1002/chem.201902916
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis of Magnetic Nanoparticles for Permanent Magnet Applications

Abstract: Permanentm agnets are ac lass of critical materials for information storage, energy storage, and other magnetoelectronic applications. Compared with conventional bulk magnets, magnetic nanoparticles (MNPs) showu nique sizedependentm agnetic properties, which make it possible to control and optimize their magnetic performance for specific applications. The synthesis of MNPs has been intensively explored in recent years. Among different methods developed thus far,c hemical synthesis based on solution-phase react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 74 publications
0
20
0
Order By: Relevance
“…This mode of imaging is often used to study nanoparticles containing higher atomic number(s) and/or compositional variations, e.g., core-shell nanoparticles [51][52][53] . Magnetic nanoparticles, such as those of iron, exhibit unique magnetism that can be systematically tuned by their size and shape, and as a result have been extensively researched for applications in data storage 54 , catalysis 55 and biomedicine 56,57 properties are ideally suited for use in bio-imaging and magnetic hyperthermia.…”
Section: Core-shell Nanoparticles With Irregular Shape Variantsmentioning
confidence: 99%
“…This mode of imaging is often used to study nanoparticles containing higher atomic number(s) and/or compositional variations, e.g., core-shell nanoparticles [51][52][53] . Magnetic nanoparticles, such as those of iron, exhibit unique magnetism that can be systematically tuned by their size and shape, and as a result have been extensively researched for applications in data storage 54 , catalysis 55 and biomedicine 56,57 properties are ideally suited for use in bio-imaging and magnetic hyperthermia.…”
Section: Core-shell Nanoparticles With Irregular Shape Variantsmentioning
confidence: 99%
“…It has been widely reported that particle size, shape, composition, and structural defects are important factors that strongly influence the magnetic behaviors and, consequently, applications of the CoFe 2 O 4 nanoparticles [14,15]. For example, the ferromagnetic CoFe 2 O 4 nanoparticles have the advantages for permanent magnet applications such as magnetic recording and energy storage [16], while the superparamagnetic CoFe 2 O 4 nanoparticles have the merits for biomedical applications such as hyperthermia treatment, drug delivery, and cancer therapy [17]. The CoFe 2 O 4 nanoparticles could be synthesized by various methods including sol-gel combustion [18], thermal decomposition [19], co-precipitation [5], microemulsion [20], and solvothermal [21] and polyol [22] approaches.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33] Moreover, the potential advantages of heterogeneous catalysis, including non-tedious recycling process, easy process handling, overall lower costs, the minimization of toxic metal in products, and furthermore, in some cases they are even more selective than homogeneous counterparts. [34,35] Among all heterogeneous catalysts, superparamagnetic nanoparticles have been intensively considered due to their large surface area and scientific applications including magnetic field assisted transport, [36] medical imaging, [37] drug delivery, [38] and magnetic bioseparations. [39] However, having magnetic dipolar attractions in naked magnetic nanoparticles (MNPs) such as magnetite (Fe 3 O 4 ), the aggregation of pure MNPs is unlikely inevitable.…”
Section: Introductionmentioning
confidence: 99%